Spirituality Business with Faith - Suraji, Robertus; Sastrodiharjo, Istianingsih (HM Publisher, 2022)
Several studies have found that many business activities ignore human values ​​and damage the environment. This condition shows that business people ignore the spiritual factors in their activities. Therefore, it is a question of whether it is possible to combine business with spirituality so that business brings blessings to other people and their environment. The notion that business is contrary to religion has long been happening. Karl Mark considers that religion is an obstacle to economic development. However, Marx Weber's research proves that Protestantism in Europe and America can be a driver for the birth of capitalism. The modern economic theory finds that we will find saints, mystics, or Sufis in companies in the era of global markets. The business spiritual has taught that business is not just a matter of making money. However, there must be a balance between spiritual and material values ​​and respect for the human condition of future generations. In Islam, the union of business with the spiritual is not new. This fact is very clearly exemplified by the Prophet Muhammad. and his friends. The Prophet and the Companions did not separate business activities from spiritual values. A healthy business brings balance, as stated in Surah Ar-Rahman verses 7-9; the earth and sky were created in balance. Humans are prohibited from destroying the balance. In modern science, Elkington describes this balance in what is referred to as the Triple Bottom Line (TBL) between Profit, People, and Planet. To achieve the entire balance, Elkington's TBL in 3P (Profit, People, and Planet) must be added by 1 P, which is Prophet (Prophet). This Prophet guides business people to have spirituality, which is always their strength and awareness.